Interplay between BMI, gender, and gallstone formation: insights from an Iraqi cohort - Khalid Abbood, Mohammed; Alauldeen Khalaf, Hasan; Mohammed Ali, Hiba; Khalaf Hasan, Ali (Pharmakeftiki, 2025)
Gallstone disease (GD; also known as cholelithiasis) is a prevalent illness with many aggravating factors; it is firmly connected with metabolic abnormalities associated with insulin resistance, being overweight, hypertriglyceridaemia, and dietary propensities. Patients at risk of developing cholelithiasis are usually women, of increasing age, and suffering from diabetes mellitus. This study was performed at the Al-Yarmouk Teaching Medical Hospital in Baghdad, Iraq, between January 2020 and December 2021. It involves 250 participants: 103 obese, 100 overweight, and 47 normal-weight patients. The patients’ gender, weight, height, and body mass index (BMI) were recorded and studied. Statistical analysis revealed a strong association (p<0.05) between BMI and gallstone formation. Gender also plays a significant role, where women exhibited a higher incidence (p=0.002) than men. Age also significantly correlated with GD development risk (p=0.02). Although demographics and hormonal factors were significant, clinical evaluations revealed a high correlation between BMI and the incidence of GD. The increase in BMI leads to an increase in the incidence of cholelithiasis. Further study into the genetic and environmental factors associated with Middle Eastern populations are essential in order to enhance our understanding regarding this pathological condition and to inform our interventions.